Building Systems Integration Capabilities: The Role of the Royal Netherlands Navy in Constructing and Innovating Warships, 1945-2024 - te Kulve, Haico; Smit, Wim A. (The Northern Mariner / Le marin du nord, 2024)
This paper examines how the Royal Netherlands Navy (RNLN) dealt with the restoration of a sizeable domestic industry capable of constructing and designing complex warships since the end of WWII. Given the relatively small size of the country and the high speed of naval technological change since 1945, the restoration was not self-evident, certainly not because of the ruined state of that industry. We argue that the development of systems integration capabilities played a key role in the restoration. By zooming in on the strategies of the Navy to support the development of systems integration capabilities we seek to understand how the Dutch naval sector developed since 1945. We show that the ability of the Navy to support the acquisition and maintenance of systems integration capabilities depended on both domestic and international political and commercial dynamics and that systems integration capabilities could also be lost. Le présent article analyse les efforts déployés par la Marine royale néerlandaise pour restaurer une industrie nationale importante capable de concevoir et de construire des navires de guerre complexes depuis la fin de la Seconde Guerre mondiale. Compte tenu de la taille relativement petite du pays et de l’évolution rapide des changements technologiques navals depuis 1945, la restauration n’allait pas aller de soi, notamment parce que l’industrie avait été laissée en ruines. Nous soutenons que le développement des capacités d’intégration des systèmes a joué un rôle clé dans la restauration. En mettant l’accent sur les stratégies de la Marine visant à appuyer le développement des capacités d’intégration des systèmes, nous cherchons à comprendre comment le secteur naval néerlandais s’est développé depuis 1945. Nous indiquons que les habiletés de la Marine à favoriser l’acquisition et la maintenance des capacités d’intégration des systèmes dépendait de la dynamique politique et commerciale sur le plan national et international et que les capacités d’intégration des systèmes pouvaient également se perdre.